Effect of Nauclea subdita (Korth.) Steud. leaf extract on hematological and histopathological changes in liver and kidney of striped catfish infected by Aeromonas hydrophila - Siti Aisiah (Veterinary World, 2020)
Aim: The present study was conducted to investigate the efficacy of different doses of Bangkal (Nauclea subdita) leaf extract on hematological and histological changes in kidney and liver of catfish (Pangasius hypophthalmus) infected by Aeromonas hydrophila.